Is uptake of disability-related social security benefits modified by demographic, social and area-level factors? - Dermot O'Reilly; Michael Rosato; Aideen Maguire (International Journal of Population Data Science, 2018)
Introduction In the UK Disability Living Allowance (DLA) provided a non means-tested contribution towards the disability-related costs of living for disabled people aged